Major Histocompatibility Complex Class I‐Related Chain A Alleles and Histology of Nonalcoholic Fatty Liver Disease. Issue 1 (30th September 2020) - Karrar, Azza; Rajput, Bijal; Hariharan, Siddharth; Abdelatif, Dinan; Houry, Mohamad; Moosvi, Ali; Ali, Irfan; Tan, Daisong; Noor, Sohailla; Esmaeili, Donna; Felix, Sean; Alaparthi, Lakshmi; et al.
Abstract : Major histocompatibility complex class I‐related chain A (MICA) is a highly polymorphic gene that modulates immune surveillance by binding to its receptor on natural killer cells, and its genetic polymorphisms have been associated with chronic immune‐mediated diseases. The progressive form of nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH), is characterized by accumulation of fat and inflammatory cells in the hepatic parenchyma, potentially leading to liver cell injury and fibrosis. To date, there are no data describing the potential role of MICA in the pathogenesis of NAFLD. Therefore, our aim was to assess the association between MICA polymorphism and NASH and its histologic features. A total of 134 subjects were included. DNA from patients with biopsy‐proven NAFLD were genotyped using polymerase chain reaction–sequence‐specific oligonucleotide for MICA alleles. Liver biopsies were assessed for histologic diagnosis of NASH and specific pathologic features, including stage of fibrosis and grade of inflammation. Multivariate analysis was performed to draw associations between MICA alleles and the different variables; P ≤ 0.05 was considered significant. Univariate analysis showed that MICA*011 (odds ratio [OR], 7.14; 95% confidence interval [CI], 1.24‐41.0; P  = 0.04) was associated with a higher risk for histologic NASH. Multivariate analysis showed that MICA*002 was independently associated with a lower risk for focal hepatocyte necrosis (OR, 0.24; 95% CI, 0.08‐0.74; P  = 0.013) and advanced fibrosis (OR, 0.11; 95% CI, 0.02‐0.70; P  = 0.019). MICA*017 was independently associated with a higher risk for lymphocyte‐mediated inflammation (OR, 5.12; 95% CI, 1.12‐23.5; P  = 0.035). Conclusion: MICA alleles may be associated with NASH and its histologic features of inflammation and fibrosis. Additional research is required to investigate the potential role of MICA in increased risk or protection against NAFLD.